1987
DOI: 10.1177/001698628703100207
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Attitudes and Practices Between Fathers of Young Gifted and Fathers of Young Non-Gifted Children: A Pilot Study

Abstract: An interview protocol containing 119 items was administered to identify patterns of attitudes and practices among fathers of young gifted children (N = 9) which differed from those among fathers of young nongifted children (N = 10). Although there were many similarities, differences were observed in six thematic areas: general involvement, reading emphasis, orallanguage emphasis, psychomotor emphasis, concern for the child's self-esteem, and push for independence.Implications for educational practice and for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
4

Year Published

1989
1989
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 9 publications
2
11
0
4
Order By: Relevance
“…Tako visoka usaglašenost odlikuje rezultate istraživanja uloge afektivne responsivnosti roditelja u razvoju talenta, otuda što se topao i prihvatajući stav roditelja pokazao dosledno povezanim sa visokim stepenom ostvarenosti detetovih potencijala (Bradly & Caldwell, 1976, Vernon, 1979, svi prema Landau & Weissler, 1993Cornell & Grossberg, 1987;Karnes & Shwedel, 1987;OlszewskiKubilius, 2002;Weissler & Landau, 1992).…”
Section: Istraživanja Porodičnih Prilika Darovite Deceunclassified
See 2 more Smart Citations
“…Tako visoka usaglašenost odlikuje rezultate istraživanja uloge afektivne responsivnosti roditelja u razvoju talenta, otuda što se topao i prihvatajući stav roditelja pokazao dosledno povezanim sa visokim stepenom ostvarenosti detetovih potencijala (Bradly & Caldwell, 1976, Vernon, 1979, svi prema Landau & Weissler, 1993Cornell & Grossberg, 1987;Karnes & Shwedel, 1987;OlszewskiKubilius, 2002;Weissler & Landau, 1992).…”
Section: Istraživanja Porodičnih Prilika Darovite Deceunclassified
“…Naime, ishodi istraživanja emocionalne povezanosti članova porodice (kohezivnost) i promenljivosti strukture moći, uloga i pravila unutar porodica sa darovitim detetom (adaptabilnost), podrazumevaju ravnomernu zastupljenost rezultata koji svedoče o važnosti ovih karakteristika porodičnog funkcionisanja u razvoju darovitosti (Abelman, 1991;Caplan, Henderson, Henderson, & Fleming, 2002;Cornell & Grossberg, 1987;Karnes & Shwedel, 1987), kao i rezultata koji negiraju posebnu vezu porodične kohezivnosti/adaptabilnosti i darovitosti (Csikszentmihalyi, Rathunde, & Whalen, 1997;Taylor, 1996, prema Schilling, Sparfeldt, & Rost, 2006West, Hosie, & Mathews, 1989). No, čak i da nema "negacijskog" korpusa nalaza i da je kontradiktornost gotovo nepostojeća, ovo područje empirije ne bilo bio lišeno poteškoća u generisanju celovitih odgovora, otuda što nam ne nudi saznanja o optimalnim nivoima porodične kohezivnosti/adaptabilnosti za razvoj darovitosti, koje mnogi teorijski modeli naširoko elaboriraju.…”
Section: Istraživanja Porodičnih Prilika Darovite Deceunclassified
See 1 more Smart Citation
“…Karnes and Schwedel (1987) interviewed the fathers of 9 gifted (140 on average on the StanfordBinet IQ test) preschool children who attended the University of Illinois Preschool Program for the Gifted and the fathers of 10 non-gifted (113 on average on the StanfordBinet IQ test) preschool children who were either not qualified for the university gifted program or enrolled in the program as non-handicapped ''models'' for handicapped children. The authors found that fathers of the gifted children emphasized more reading for their children compared to those of the non-gifted children.…”
Section: Gifted and Talented Studentsmentioning
confidence: 99%
“…M. B. Karnes and Schwedel (1987) interviewed fathers of young gifted children and cited such differences as: (1) fathers of the gifted were more likely to report reading-related activities with their children, emphasis on oral language as a tool in one's environment, participation with the children in fine motor activities; and (2) these fathers were more likely to specify strategies that they used in order not to impart a poor self-image to their children. In contrast, fathers of the nongifted were more likely to report having playground equipment around the house and reported that their child's strengths were in the psychomotor area.…”
mentioning
confidence: 99%